Utero-cuteneous Fistula: Rare Complication of Caesarean Section - Pant, Pradam Raj (Nepal Journal of Obstetrics and Gynaecology, 2013)
Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 1 / Issue 13 / Jan- June, 2012 / 66-67 DOI: http://dx.doi.org/10.3126/njog.v7i1.8842